Public Response to #JalanBerkeselamatan Campaign on TikTok: A Social Judgment Theory Analysis - Wulandari Wurjanti (FAKULTAS DAKWAH UIN SALATIGA, 2025)
This study evaluates audience responses to the #JalanBerkeselamatan digital campaign initiated by the Directorate General of Highways, Ministry of Public Works of Indonesia, through the lens of Social Judgment Theory (SJT). The campaign seeks to promote road safety awareness and shared responsibility for maintaining infrastructure, amidst ongoing challenges such as vandalism, overloaded trucks, and limited public understanding. Using qualitative content analysis of campaign videos and digital sentiment analysis of social media comments via Orange and Voyant Tools, the study investigates whether the campaign’s messages align with audience attitudes. Findings show that most responses fall within the Latitude of Non-Commitment, marked by curiosity about infrastructure and safety procedures. This highlights the need for clearer, emotionally resonant, and educational messaging. By focusing on persuasive effectiveness and public receptivity, the study contributes to expanding the discourse on digital campaigns in developing contexts and underscores the value of adaptive, emotionally framed communication strategies to foster meaningful engagement.